MATCH-MAKING AND ENGAGEMENT HABITS - TUREAC, Tatiana (Acta et Commentationes, Sciences of Education, 2019)
The primordial function of the wooing custom is to ask the girl for marriage as a gesture of rebellion addressed by the future son-in-law and his parents to the father-in –low. The wedding in the Moldavian villages, as well as the entire carpatho-danubian space is unitary from the perspective of the overall scenario. Local differentiation does not affect its structure today, the changes being non-essential. The betrothal was the next step, part of the matrimonial custom. The young boy took some money, a ring and left with the old men to the girl. The girl came forward with a plate of wheat or rice, in which the boy put his ring and money. The girl put her ring and a handkerchief embroidered with her hand.